English Language Teaching (ELT) for Students with Visual-Spatial Learning Style - Fitria, Tira Nur; Simbolon, Nurmala Elmin (JELLE, 2024)
This study describes English Language Teaching (ELT) for students with a visual-spatial learning style. This approach describes the characteristics of the phenomenon being studied in detail, in this case, ELT for students with a visual-spatial learning style. This study uses a qualitative descriptive. The analysis shows that visual-spatial learners process information primarily through visual and spatial methods, excelling in visualizing concepts and demonstrating proficiency in spatial tasks like map reading and object manipulation. They prefer learning through visual media such as diagrams and videos, which aid in their retention of information. Educators can optimize teaching for these learners by leveraging their strengths. In teaching English, strategies like using pictures, diagrams, and graphs to illustrate grammar and vocabulary help students connect English words with concrete visuals, thereby enhancing comprehension. Multimedia tools such as videos and interactive whiteboards engage students actively and facilitate understanding through visual simulations. Physical models and digital applications provide hands-on experiences that deepen their grasp of abstract English concepts. Activities like creating mind maps and storyboards reinforce learning through visual representation, fostering thorough understanding. Project-based tasks encourage creativity and holistic learning through visual presentations and concept maps, while image-based discussions improve language proficiency by linking words with visual contexts. Implementing color coding and visual systems supports systematic organization and recall of information, benefiting grammar and vocabulary learning. Creative endeavors such as creating comics or artworks allow students to express their language skills innovatively, motivating deeper engagement. By integrating these methods, educators create enriching and effective learning experiences tailored to visual-spatial learners, supporting their mastery of the English language while nurturing their strengths.